Sporadic inclusion body myositis in the rheumatology clinic - Fernando Henrique Carlos de Souza; Gustavo Luiz Behrens Pinto; Jean Marcos de Souza; Pablo Arturo Olivo Pallo; Leonardo Santos Hoff; Samuel Katsuyuki Shinjo (Indian Journal of Rheumatology)
Sporadic inclusion body myositis (sIBM) is a progressive and insidious skeletal muscle disorder characterized classically by the quadriceps, wrist, and finger flexor weakness. The main irreversible complications of sIBM are dysphagia and walking difficulties. The disease affects more men than women, and the symptom onset mainly occurs between 50 and 70 years of age. Due to its slow progression, sIBM diagnosis is frequently delayed and therefore misdiagnosed as other muscle diseases. sIBM remains refractory to treatment (e.g., glucocorticoid, and immunosuppressive/immunomodulatory/immunobiological drugs). Although there have been no robust clinical trials, training exercise/physiotherapy should be prescribed regularly in sIBM patients.